Problem Based Learning sebagai Strategi Pembelajaran Kontekstual pada Materi Ekosistem: (Studi Tindakan Kelas di SMA Katolik St. Rosa de Lima Tondano) - Limmey Maria Tambingon; Arrijani Arrijani; Musma Rukmana (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Biology education in high school has an important role in shaping students' science literacy and critical thinking skills. However, ecological material, particularly the topic of Ecosystem Components and their Interactions, is often considered difficult because it is abstract and not easy to observe directly. This research aims to improve student learning outcomes through the application of the Problem Based Learning (PBL) model, which emphasizes real problem-solving, collaborative discussion, and active involvement in the learning process. The research uses the design of Classroom Action Research (PTK) which was carried out in two cycles in class X of St. Rosa de Lima Catholic High School Tondano involving 10 students in the odd semester of the 2025/2026 school year. Data was collected through observation of teacher and student activities, learning outcome tests in the form of pretests and posttests, and learning documentation. The analysis was carried out descriptively, qualitatively, and quantitatively by calculating the average score, percentage of completion, and student involvement. The results of the study showed a significant increase. The percentage of teacher activity increased from 58.3% in the first cycle to 87.5% in the second cycle, while student activity increased from 45.83% to 83.33%. The average score of students also increased from 70% in cycle I to 90% in cycle II, with classical completeness reaching 90%. These findings confirm the effectiveness of PBL as a contextual Biology learning strategy, able to bridge ecological concepts with real life, and increase students' curiosity, cooperation, and critical thinking skills.